1987
DOI: 10.1007/bf02533944
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of cultured B16 melanoma cell variants with different lung‐colonizing potential

Abstract: Lipid components influence several cell surface properties that are critical in different stages of the metastatic process. In this study, we examined whether the different lung-colonizing potential of B16-F1 and B16-F10 melanoma cells could be related to a characteristic lipid profile. The lipid analyses, carried out on the same cell cultures used for the assay of lung-colonizing potential, revealed characteristics in the lipid composition of both B16-F1 and B16-F10 melanoma cells that are common to other sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…2, 3). Reports that B16 melanomas produce almost entirely GM3 (∼95%), with the remainder consisting of GM2, GM1, and possibly GD1a [61] support the conclusion that SBD indeed prefers high concentrations of more complex ganglioside species (such as GT1b, GD1b, or GQ1b; see fig. 4) in which this cell line is deficient.…”
Section: Resultsmentioning
confidence: 78%
“…2, 3). Reports that B16 melanomas produce almost entirely GM3 (∼95%), with the remainder consisting of GM2, GM1, and possibly GD1a [61] support the conclusion that SBD indeed prefers high concentrations of more complex ganglioside species (such as GT1b, GD1b, or GQ1b; see fig. 4) in which this cell line is deficient.…”
Section: Resultsmentioning
confidence: 78%
“…Because tumor cells rely mostly on glycolysis rather than on mitochondrial respiration (42), they are less effective than normal cells in generating ATP that is required for the internalization of exogenously added phosphatidylserine. It is also possible that integration of phosphatidylserine into plasma membrane of tumor cells from liposomes may be lessened by the specifics of their membrane lipid composition (43). We found that phosphatidylserine-containing ointment significantly inhibited tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…After conversion to prostaglandins (PG), leukotrienes, or oxygen-derived free radicals, they mediate a variety of pathological processes (1). The PUFA content is drastically decreased in hepatoma cells in comparison with normal hepatocytes (2), in glioma cells in comparison with oligodendroglia cells (3,4) and in melanoma cells (5). This deficiency may cause alterations in signal transduction and an interruption of normal cellular events (3).…”
mentioning
confidence: 98%